The Implementation of Mindfulness-Based Intervention to Overcome Anxiety in Adolescents: A Narrative Review - Serenity, Kinar; Komariah, Maria; Sriati, Aat (Universitas Fort De Kock Bukittinggi, 2023)
Background: The most common mental health problem experienced by adolescents is anxiety. Therefore, therapeutic interventions are needed, one of which is mindfulness-based interventions. This study aims to identify the types and describe the implementation of mindfulness-based interventions in overcoming anxiety in adolescents. Methods: A narrative review study design was used. The study selection process used the PRISMA Flow Diagram 2020 guide. The literature search was conducted through PubMed, Sage Journal, and Springer Link databases. Articles published from 2012 to 2021 with Randomized Controlled Trial, Quasi-Experimental, Qualitative Study, and Mixed methods study in English. According to the inclusion and exclusion criteria, there were ten articles based on the election results. Results: Mindfulness-based interventions to overcome anxiety in adolescents are Learning to BREATHE, Sleep Sense, Mindfulness-Based Stress Reduction, Mindfulness-based Stress Reduction for Teens, Mindfulness-based programs, Mindfulness Martial Arts, and Making Friends with Yourself. Conclusion: Nurses can use mindfulness-based intervention to help adolescents cope with anxiety, including high anxiety levels, Generalized Anxiety Disorder, and Trait Anxiety.Keywords: adolescents, anxiety, anxiety disorders, mindfulness